Tahfiz-Tok: Malaysian Muslim Religious Schools’ Platform Vernaculars - Emma Baulch; Benjamin Y. H. Loh (Social Media + Society)
The article examines the TikTok accounts of selected tahfiz (Muslim religious) schools in Malaysia and considers the roles and meanings attributed to children in them. Tahfiz accounts present children in two ways: as subjects who are “acted upon” (taught skills in Quranic recitation), and as “natural” subjects who appear in candid videos of mundane tahfiz life. These contrasting representations resemble those in child influencer accounts Abidin studied, which feature a calibrated oscillation between performances of skill (“anchor”) and performances of behind-the-scenes authenticity (“filler”). But the specific qualities of tahfiz “anchor” content, emphasizing moral improvement, also bear the trace of influencer accounts associated with the hijrah movement, which advocates for strict adherence to Islamic codes and practices as a preferred way of living ethically in the present. The article employs “anchor” and “filler” as analytical tools to understand the new vernaculars emerging at the intersection of these two variants of the influencer genre.